Pengaruh Faktor Ekonomi dan Teknologi terhadap Pertumbuhan E-Commerce Lintas Batas di Indonesia (2013-2023) - Saptarina, Martha; Zhang, Jie (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Cross-border e-commerce has emerged as a fundamental component of the global digital economic change, particularly in Indonesia. Macroeconomic dynamics and the acceleration of digitalization over the past decade have influenced this development. This study aims to analyze the influence of economic factors, such as Gross Domestic Product (GDP) per capita, inflation, and exchange rates, along with technological factors like internet penetration and digital wallet usage, on the growth of cross-border e-commerce in Indonesia. This study uses secondary data from the period 2013 to 2023. The analysis method used is log-linear regression with the Ordinary Least Squares (OLS) approach, accompanied by classical assumption testing to ensure the validity of the model. The results show that only GDP per capita and inflation significantly affect the growth of cross-border e-commerce, with a coefficient of determination (R²) value of 0.8682, indicating that these two variables can explain 86.82% of the variation in cross-border e-commerce growth. GDP per capita has a positive and significant effect, confirming the role of people's purchasing power and the growth of the middle class in driving cross-border digital trade activities. Meanwhile, inflation is also significant, showing a positive trend, reflecting consumption substitution behavior where consumers switch to cross-border products when domestic prices increase. The variables of exchange rate, internet penetration, and digital wallet usage are not significant in the model due to the high correlation between variables, causing multicollinearity. These results emphasize the importance of macroeconomic stability and inflation control in supporting cross-border e-commerce growth in Indonesia.